Improved Low-Frequency Noise in Recessed-Gate E-Mode AlGaN/GaN MOS-HEMTs Under Electrical and Thermal Stress - Qianlan Hu; Chengru Gu; Dan Zhan; Xuefei Li; Yanqing Wu (IEEE Journal of the Electron Devices Society, 2021)
1/f noise provides essential information on the interface trapping effect as well as the scattering mechanism in transistors. In this work, a systematic 1/f noise study has been carried out on the recessed-gate enhancement-mode (E-mode) GaN MOS-HEMTs under electrical and thermal stress together with the depletion-mode (D-mode) counterpart. Low-frequency (1–1000 Hz) measurement has been performed at room (25 °C) and elevated (100 °C) temperatures at different carrier densities at the drain bias of 2 V and 10 V. The results show the E-mode device has much better noise characteristics under high voltage and high temperature compared with the D-mode counterpart. Moreover, charge-noise model reveals that the improved noise behavior of the E-mode device at high density and high drain bias at 100 °C originating from the energy band alignment at high biases, where the D-mode device suffers from extra charge trapping scattering in the gate edge near the gate-to-drain access region.